2017
DOI: 10.1128/genomea.01002-17
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality Genome Sequence of Bacillus anthracis Strain 14RA5914 Isolated during an Outbreak in Germany in 2014

Abstract: Bacillus anthracis is a zoonotic agent causing anthrax, a notifiable disease in animals. The last anthrax outbreak among cattle in Germany occurred in April 2014 in Saxony-Anhalt. Here we report a high-quality genome sequence of the Bacillus anthracis strain 14RA5914 Dobichau isolated from the spleen of a dead cow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…This data set (total = 43) includes (i) eight epidemiologically related strains from the three most recent anthrax outbreaks in Germany in 2009, 2012, and 2014, as well as (ii) 35 epidemiologically unrelated strains from 35 different outbreaks in Italy with one strain per outbreak (Table S1). Strains of this data set were sequenced in this study, except three German strains previously sequenced using the Ion Torrent or Pacific Bioscience platform ( 23 25 ). Data Set 3 includes 57 published B. anthracis strains isolated from heroin users in four European countries ( 26 ) (Table S1) and was used to evaluate the proposed cutoff for clustering.…”
Section: Methodsmentioning
confidence: 99%
“…This data set (total = 43) includes (i) eight epidemiologically related strains from the three most recent anthrax outbreaks in Germany in 2009, 2012, and 2014, as well as (ii) 35 epidemiologically unrelated strains from 35 different outbreaks in Italy with one strain per outbreak (Table S1). Strains of this data set were sequenced in this study, except three German strains previously sequenced using the Ion Torrent or Pacific Bioscience platform ( 23 25 ). Data Set 3 includes 57 published B. anthracis strains isolated from heroin users in four European countries ( 26 ) (Table S1) and was used to evaluate the proposed cutoff for clustering.…”
Section: Methodsmentioning
confidence: 99%
“…The Italian isolates represent a wide section of strains, which are different from each other in terms of location and year of isolation (from 1917–2017), as well as genetic profiles (different genotypes and lineages) (see Table S1 ). The German, as well as the Italian strains, have been described in previous publications [ 16 , 17 , 18 ]. Previous analyses based on classical canonical SNP typing and core genome MLST have shown that the two German strains belong to the Ames/Sterne canSNP group [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The last human infections in 2012 were associated with illicit consumption of heroin allegedly contaminated with B. anthracis spores ( 6 8 ). Animal cases are equally rare, with small-scale bovine outbreaks recorded in 2009 ( 9 ), 2012 ( 10 ), and 2014 ( 11 ). While these animal cases involved B. anthracis genotypes common in Germany, the human cases raised concern, as the genotypes involved were distinct from any known German isolate but closely related to strains from the Near and Middle East ( 12 ).…”
Section: Introductionmentioning
confidence: 99%